Route scouting and optimization of a potent sulfoximine-based inverse agonist of RORγt. Issue 40 (4th October 2018) - Lafitte, Guillaume; Parnet, Veronique; Pierre, Romain; Raffin, Catherine; Vatinel, Rodolphe; Musicki, Branislav; Tomas, Loic; Bouix-Peter, Claire; Ouvry, Gilles; Daver, Sebastien; Arlabosse, Jean-Marie; Boiteau, Jean-Guy; et al.
Abstract: During our research looking for novel inverse agonists of RORγt, we identified a potent sulfoximine-based modulator as one of our pre-clinical candidates for the topical treatment for psoriasis. Herein, we describe the various routes we evaluated during the lead generation and optimization phases and the final route chosen for scale-up to deliver the first 100 g of API. Graphical abstract: